Dental digital impressions with intraoral scanners: a review of the literature - Palomino-Granados, Roberto Carlos (2024)
Computer-aided design and computer-aided manufacturing (CAD-CAM) has been applied in dentistry for the preparation and analysis of various dental treatments. It starts with capturing images through intraoral scanners, having different types of software and image export systems and technology. The advantages of this digital workflow are the following: better adjustment, shorter clinical time, and speed in dental treatments, in addition to providing greater practicality for dental surgeons. The accuracy he provide is clinically acceptable in comparison with conventional methods, so there is sufficient evidence for their validity; however, it should be taken into account that several factors can alter the result, such as the operator's experience, the type of scanner, the type of software, the software update, the scanning principle of the scanner, the environment, the scanning sequence, and the oral structures. The present review article aims to analyze the literature on the different characteristics and properties that intraoral scanners present today and the evidence of the potential benefits and accuracy of digital impression techniques versus conventional impression techniques.